Urinary Cytology: Potential Role in Canine Urinary Tract Infections - Ilaria Lippi; Verena Habermaass; Eleonora Gori; Valentina Virginia Ebani; Alessio Pierini; Veronica Marchetti (Veterinary Sciences, 2022)
The diagnosis of urinary tract infections (UTIs) requires a concomitant evaluation of clinical signs and urine culture, which is of fundamental to start an appropriate antibiotic treatment. Several factors, such as subclinical bacteriuria or pre-analytical errors, may make the interpretation of urine culture difficult. The aim of the study was to evaluate the association between the finding of neutrophils and bacteria in unstained and stained canine urine sediment and the presence of clinical signs and positive urine culture. Urine samples from 35 dogs with clinical signs of UTI and 55 asymptomatic dogs with risk factors for UTI were prospectively collected by cystocentesis, divided into three aliquots, and submitted for: (1) physical and chemical Dipstick analysis and unstained urinary sediment (casts, crystals, bacteria, leucocytes, cells, parasites); (2) stained urinary sediment (extra/intracellular bacteria, degenerated and non-degenerated neutrophils); (3) qualitative and quantitative urine culture and antimicrobial sensitivity-test. The association between unstained and stained findings of urinary sediment and urine culture was tested. Sensibility, specificity, and positive/negative predictive values in diagnosing positive urine cultures of bacteria at unstained and stained evaluation were compared. Both wet-mount bacteriuria and the cytological presence of intracellular and extracellular bacteria, neutrophils, and degenerated neutrophils were successively associated with positive urine culture (p < 0.001). The presence of intracellular bacteria was the only independent predictor of positive urine culture. Total bacterial count did not differ significantly between symptomatic and asymptomatic dogs. Detection of extracellular and intracellular bacteriuria at stained urinary sediment significantly improved the sensibility of predicting positive urine culture. Cytologic evaluation of urinary sediment may be helpful in detecting signs of active inflammation, thus enhancing the clinical relevance of a positive urine culture.